ANALISIS INDETIFIKASI TEORI USAHA DAGANG SEBAGAI KORPORASI DALAM KASUS ILLEGAL LOGGING (STUDI TINDAK PIDANA PENGADILAN NOMOR 12/Pid.SUS-LH/2021/PN.KSN): Analysis theoretical identification trading businesses as corporations in illegal logging (Study of Criminal Act Decision No. 12/Pid.SUS LH/2021/PN.KSN) - Muhamad Akbar Asanudin; Maria Silvya Elisabeth Wangga (Reformasi Hukum Trisakti, 2025)
Environmental crimes involving corporations in Indonesia can lead to deforestation with physical and economic impacts, such as in the case of Illegal Logging. These actions violate legal provisions stated in Law Number 18 of 2013. For example, in 2020, in the village of Tumbang Tiran, the business entity Unit Dagang Karya Abadi, represented by Ripansyah as the Owner/Responsible Party, was found guilty of committing an Illegal Logging crime that violated Article 83 Paragraph (4) letter a in conjunction with Article 12 letter d of Law Number 18 of 2013. The issue raised in this article is the role of business enterprises or corporations in Illegal Logging cases (based on the Cassation Decision of the Kasongan District Court Number 12/Pid.Sus-Lh/2021/Pn.Ksn), and the corporate responsibility for such environmental crimes. This study uses a normative juridical approach, analyzing primary and secondary legal sources. This research is descriptive, with data analyzed qualitatively, and using deductive reasoning to draw conclusions. The results and conclusions, based on Article 1 Paragraph 22 of Law Number 18 of 2013, categorize Unit Dagang Karya Abadi as a corporate legal subject that can be held accountable for environmental crimes.